Dakwah Pendidikan Kyai Haji Muhammad Ilyas Ruhiat (Ajengan Cipasung) - Arifin, M Jaelani; Husna , Bagya; Nahdia Lulu Annawawie, Aniq; Murodi; Yakin, Syamsul (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2024)
This research aims to examine the significant role of Kyai Haji Muhammad Ilyas Ruhiat in Islamic educational dakwah through Pondok Pesantren Cipasung. Kyai Ilyas, a prominent scholar known for his moderate and inclusive approach, successfully modernized the pesantren education system by integrating religious knowledge and general sciences. His educational dakwah not only focused on religious teachings but also shaped the character of students to be prepared for global challenges. This study employs a descriptive biographical method, where data is gathered from relevant literature and analyzed to gain a deeper understanding of Kyai Ilyas's dakwah strategies. The findings show that his approach to pesantren education has become a model for Islamic educational development in Indonesia and significantly contributes to the formation of a well-mannered and knowledgeable society.